Endothelium condition and role of immunocompetent cells in atherosclerosis development as a cause of ischemic stroke - Chuiko, Nataliia (ScienceRise: Medical Science, 2020)
The aim. To determine the state of the cerebral vascular endothelium and the role of immunocompetent cells in the ischemic stroke development on the background of atherosclerosis. Materials and methods. We studied cerebral vessels of 50 deaths with ischemic cerebral infarctions, 50 – with severe cerebral atherosclerosis without CVD (cerebrovascular disease) manifestation and 50 deaths, whose cause of death was not related to CVD and atherosclerosis (control group). Histological preparations of vessels were stained with hematoxylin-eosin and Masson Trichrome, and also immunohistochemical study was conducted using CD31/PECAM-1 (Endothelial Cell Marker) Ab-1, CD4 (CD4 Ab-8), CD8 (SP 16), CD20 (CD20 Ab-1) CD68 and (CD68/Macrophage Marker Ab-4) markers. Results. Under ischemic strokes and severe atherosclerosis the cerebral vessels endothelium acquires structural changes in form of rupture, desquamation and exfoliation, formation of desquamated endothelial cells clusters. Speaking of endothelial damage, it should not be supposed that changes should occur at the macroscopic level only, endothelial damage at the cellular level shall be sufficient enough. Immunocompetent cells are of key importance in atherosclerosis development; adhesion on the luminal surface of arteries, presence of a large number of these cells under the endothelium and of more mature macrophages in the intima depth indicates the influx of these cells, which actively potentiate atherosclerosis formation, from the blood into the artery wall. Conclusions. Disorders of the endothelial lining with changes in endothelial cells morphology contribute to the atherosclerotic plaque development. Lymphocytes and macrophages form the molecular basis of many important processes, including the inflammatory response and the immune response